Erythromycin as a prokinetic agent in preterm neonates: a systematic review. Issue 4 (17th May 2005) - Patole, S; Rao, S; Doherty, D
Abstract : Background: It often takes several days or even weeks to establish full enteral feeds (FEFs) in preterm, especially extremely low birthweight neonates because of feed intolerance related to gastrointestinal hypomotility. Clinical trials of erythromycin as a prokinetic agent in preterm neonates have reported conflicting results. Aim: To systematically review the efficacy and safety of erythromycin as a prokinetic agent in preterm neonates. Methods: Only randomised controlled trials in preterm neonates (gestation ⩽37 weeks) were considered eligible for inclusion. The primary outcome was the time to reach FEFs of 150 ml/kg/day. The secondary outcomes included the incidence of erythromycin related adverse effects such as diarrhoea, cardiac arrhythmias, and hypertrophic pyloric stenosis. No restrictions were applied on the dose (low: 3–12 mg/kg/day; antimicrobial: ⩾12 mg/kg/6–8 hours) and route (oral or intravenous) and mode (prophylactic or rescue) of administration. The standard methodology for systematic reviews was followed. A subgroup analysis was preplanned based on the dose and mode of drug administration. Results: Seven trials (three prophylaxis, four rescue) with various doses, routes and modes of administration, and durations of erythromycin treatment and different results were found to be eligible for inclusion in the analysis. Meta-analysis could not be performed, as specific data were either inadequate or not available. Conclusion: The conflicting trial results may be explained by differences in dose and route and mode of administration of erythromycin and in gastrointestinal motor responses in the presence of different feeding conditions—for example, fasting v fed state, intermittent v continuous feeds. Gestational and postnatal ages during erythromycin treatment are also important.